A RESULT OF THE STUDY ON CANINE TUMORS IN ULAANBAATAR CITY (Mongolian Journal of Agricultural Sciences, 2015)
There are some studies available on the value of cytologic examination as a diagnostic method for tumors in dogs. Therefore objectives of this study were to determine whether cytologic findings in fine-needle aspirate specimens of canine tumors correlate with histopathologic results and to find out most common tumor in dog. Information was collected from dog owners and vets according to a questionnaire, a patho-morphologic investigation of tumors was done by using cytological(Fine Needle Aspirate)and histological (MNS 5451:2005)techniques, and the gathered information was analysed. In total of 33 canine (Canis Lupus familiaris) tumor cases were found in chosen vet clinics during the time between Dec 2013 and Aug 2014. The results of histopathological, cytologicaland physical examinations revealed that 27 cases (93.1%) were a benign tumor. And maximum incidence of tumors was mammary adenoma (31%), followed by skin fibroma (27.6%), peri anal adenoma (13.8%), testicular adenoma (10.3%), soft tissue sarcoma (6.9 %), and prostate tumor, lipoma and TVT (3.4% each).Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 13-18